Znak Dziedzictwa Europejskiego jako narzędzie konstruowania dziedzictwa - Sury, Bartłomiej (Studia Etnologiczne i Antropologiczne, 2014)
This essay illustrates not only an initiative of yielding The European Heritage Label, but also the significance of that enterprise for the objects placed in the territory of Central-Eastern Europe. The cultural European Union project described in the article shows ambitious efforts of that institution in counscious creation of the own heritage. One of the aims of yielding The European Heritage Label is enforcement of effiliation with European Union among European citizens especially young people. In this context the important issue is the question of effectiveness of this enterprise.